DETERMINAN PERNIKAHAN USIA DINI - Tuti Yelvianti; Sarah Handayani (Politeknik Kesehatan Kementerian Kesehatan Banten, 2021)
Early marriage is a phenomenon that not only occurs in the country, but this phenomenon also occurs in other parts of the country. Indonesia is a developing country which includes a country with a high percentage of early marriage in the world. This paper aims to determine what factors are the most dominant in the practice of early marriage. The method that the author uses is the Literature review method by tracing article material related to the determinants of early marriage. After reviewing the articles studied, the authors get the results, that a person's level of education and knowledge has an effect or has a significant relationship with early marriage behavior. Thus, the authors conclude that one way to reduce the rate of early marriage is through education. Indonesian children must be led to do 12 years of compulsory education and even get to college.